ESTRATÉGIA DE PREVENÇÃO DE INFECÇÃO RELACIONADA À ASSISTÊNCIA À SAÚDE: GERENCIAMENTO DE COLCHÕES - Alessandra Lyrio Barbosa Giroti (2023)
Mattresses, despite being considered “non-critical” articles, represent a risk due to direct contact with the microbiota of the patient's skin and body fluids, and may become reservoirs and source of contamination. The objective was to analyze the management of mattresses in hospital beds and long-term care facilities for the elderly (ILPI) and to evaluate their physical conditions in the context of the prevention of infection related to health care, in Campo Grande/MS. This is a cross-sectional, analytical, quantitative study carried out in 18 services (five ILPI and 13 hospitals) and with a sample of 278 mattresses obtained by proportional stratified sampling. In hospitals, mattresses for clinical, surgical and pediatric beds were included, and those with bedridden patients were excluded. Indicators of conditions of use were obtained using two validated instruments. The first involved a structured interview with the professional responsible for mattress management and the second involved an integrity assessment. The collected data were organized and tabulated in Google Forms and in Google Sheets spreadsheets. Descriptive statistical analysis was represented by absolute and relative frequency and 95% confidence interval, calculation of the mean and standard deviation, in addition to the minimum and maximum values in the mattress evaluation score. To compare different groups, the Mann Whitney Test and the Kruskal Wallis Test were used, followed by the Dunn Test, as well as the Multiple Regression Analysis to analyze the scores of the evaluation criteria. Statistical analysis was performed using Epi-info™ 7.2.4 and Bio Estat 5.3. The results showed that acquisition by direct purchase prevails (94.4%), with an average frequency of 1 to 5 years (50%). The mattresses purchased are made of foam and 83% of the services mentioned the use of waterproof coverings made of nappa and corvin. Aspects associated with user comfort, material resistance and the cleaning process were frequently considered by participants. As for the evaluation of foam and coating integrity, during concurrent cleaning (38.9 and 50%, respectively) was the most mentioned moment. Only 11% of the sample had a label, 98.5% had a waterproof coating and 27.9% had the minimum required thickness. Only 9.9% of mattresses were approved, with higher approval in ILPI than in hospital, higher in private than philanthropic and public services and higher in services with fewer beds. Surgical bed mattresses were less approved than clinical and pediatric ones. In addition, mattresses purchased through bidding and evaluated by nurses were more approved. It is concluded that there is no consensus in health services regarding safety management in the use of mattresses based on acquisition principles, as well as on indicators for evaluating the integrity and preservation of mattresses. Added to this fact is the lack of knowledge on the part of professionals in relation to routines aimed at care for the patient's bed. Descriptors: beds; cross infection; disinfection; homes for the aged; patient safety.